Sharing Less Commonly Taught Languages in Higher Education Collaboration and Innovation - Heidrich Uebel, Emily; Kraemer, Angelika; Giupponi, Luca (Taylor & Francis, 2024)
This edited volume highlights how institutions, programs, and less commonly taught language (LCTL) instructors can collaborate and think across institutional boundaries, bringing together voices representing different approaches to LCTL sharing to highlight affordances and challenges across institutions in this collection of essays. Sharing Less Commonly Taught Languages in Higher Education showcases how innovation and reform can make LCTL programs and courses more attractive to students whose interests and needs might be overlooked in traditional language programs. The volume focuses on how institutions, programs, and LCTL instructors can work together, collaborating and thinking across institutional boundaries to explore innovative solutions for offering a wider range of languages and levels. With challenges including instructor isolation, difficulty in offering advanced courses or sustaining course sequences, and minimal availability of pedagogical materials compared to commonly taught languages to overcome, this collection is a vital resource for language educators and language program administrators.